2019
DOI: 10.1017/s0967199419000674
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of kaempferol toin vitromaturation medium regulates oxidative stress and enhances subsequent embryonic developmentin vitro

Abstract: SummaryKaempferol (KAE) is one of the most common dietary flavonols possessing biological activities such as anticancer, anti-inflammatory and antioxidant effects. Although previous studies have reported the biological activity of KAE on a variety of cells, it is not clear whether KAE plays a similar role in oocyte and embryo in vitro culture systems. This study investigated the effect of KAE addition to in vitro maturation on the antioxidant capacity of embryos in porcine oocytes after parthenogenetic activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Caspase-3 is an important mediator of apoptosis (Ohnishi et al, 2019) and KAE has been proven to reduce apoptosis in early porcine embryos by blocking caspase-3 expression (Y. Zhao et al, 2020). Among genes regulating apoptosis, Bax and Bcl-2 are the most important.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-3 is an important mediator of apoptosis (Ohnishi et al, 2019) and KAE has been proven to reduce apoptosis in early porcine embryos by blocking caspase-3 expression (Y. Zhao et al, 2020). Among genes regulating apoptosis, Bax and Bcl-2 are the most important.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids are polyphenols that protect plant cells against microorganisms, insects, and UV irradiation. Previous studies have shown that flavonoids such as kaempferol and quercetin exert antioxidant effects on mammalian oocytes ( Cao et al, 2020 ; Zhao et al, 2020 ). Lut, a flavone in the flavonoid group, also exhibits antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, at a concentration of 10 μM, it could enhance the primordial follicle activation, cell proliferation and oocyte meiotic resumption in the ovine cultured follicles (Santos et al, 2019). Similarly, at 0.1μM concentration, KAE was effective in increasing the blastocyst number as well as its formation rate in porcine cultured follicles (Zhao et al, 2019). Likewise, at 1µM concentration KAE was proven to be an effective agent by increasing the follicle diameter and oocyte growth in mammals (Zhou et al, 2015).…”
Section: Bioactive Compounds Kaempferolmentioning
confidence: 96%
“…Through this pathway, KAE exerts its effects on the culture of ovine preantral follicles in-vitro (Santos et al, 2019). Besides this, another mechanism of KAE is to increase the mRNA expression levels of COX2 and SOX2 genes which have a role in embryonic developmentwith a significant reduction in the Caspase-3 levels (Zhao et al, 2019). This further, helps in the improvement of zygote development in porcine cultures (W hite et al, 2016).…”
Section: Bioactive Compounds Kaempferolmentioning
confidence: 99%